Analisis Aktivitas Pariwisata Berbasis Ekonomi Kreatif di Desa Wisata Krebet, Kalurahan Sendangsari - Riyana, Nur Rizka Riyana; Tika Dwi Istiani; Irfa Rosyi Safira; Hanif Mahmud Abdullah; Gerry Katon Mahendra; Bhakti Gusti Walinegoro (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2025)
The villagers of Krebet Tourism Village initially had a livelihood of farming which later developed its economy with development of the tourism sector. This development has brought progress to the Krebet Tourism Village which attract tourists to learn and make crafts. In addition, the Krebet Tourism Village has received several awards such as the best tourist village award in Yogyakarta in 2024. This study aims to determine the practice of sustainable tourism in the Krebet Tourism Village through the Environmental Sustainability Aspect, the Economic Sustainability Aspect, and the Socio-Cultural Sustainability Aspect. The method used in this study uses qualitative descriptive. The sources of this study are websites and related articles. As well as data analysis techniques in this study are data presentation, data reduction, and drawing conclusions. The results of the study show that the Krebet Tourism Village is able to utilize the existing natural resources by making crafts in the form of wooden batik which is now well-known not only in Yogyakarta, but also famous outside the city. Tourism in the Krebet Tourism Village makes a positive contribution to several aspects including the environmental sustainability aspect, the economic sustainability aspect, and the socio-cultural sustainability aspect. In terms of environmental sustainability, the Krebet Tourism Village holds several tourism initiatives such as tree planting or farming tour packages. Tourism activities in Krebet Tourism Village have also contributed to improving the economy and welfare of the community by opening up job opportunities, one of which is wooden batik craftsmen. This is also supported by Krebet Tourism Village which is able to build community participation and active roles as a form of human resource management in the village. Now Krebet Tourism Village has been visited by many tourists to learn about the history and how to make wooden batik crafts. This positive trend was hope to be maintained and can be well managed by the Krebet Tourism Village community so that in the future it can continue to be a reference for tourism from outside the region and be an example for other tourist villages. Keywords: Tourism Village; Tourism; Creative Economy.